HUMAN RIGHTS: REALITY OR DELUSION IN PALESTINE? - Mahwish Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
Rights are all the things that can be said to be legal and deemed appropriate by the law and/or legislation of a particular government in a country. It may also be defined as basic freedom and/or autonomy that all individuals of a state may be entitled to. Although experts define the term ‘Human Rights’ to be more in perspective and relativity. This article explores the meaning and concept of human rights in today’s artificially intelligent world, illustrating the artificial existence of human rights’ champions of the world. The aim is to scrutinize the looming question of what happens to the existence of such organisations and the powers invested within them, when it comes to Palestine and the ongoing active genocide there, now for the past 200+ days. Since October 2023 the world has witnessed the unfolding of some of the most unfathomable war crimes in Gaza, the coastal strip of Palestine. Never have any reporters been denied access in such areas for news coverage as these are part of Reporters’ protocol for media coverage and share news alerts with the world. However, when this basic right and freedom of speech was snatched away by the Israelists, it was then that the men and women, as young as 22 and 25, like Motaz aziz, stood up to fight for their right and freedom of speech through the lens of their smartphones, shooting the most drastic reality that mankind could never imagine, the inhuman side of humans. With esteemed organisations and groups of activists working worldwide as part of UNICEF and ICJ, it becomes an incredulous reality when the world watches the Gaza tragedy unfold right within their eyes through the social media lens today. According to the United Nations, 1.7 million people are internally displaced, or about 75 percent of Gaza’s 2.2 million residents. The displacement itself has led to immense challenges for the population and the humanitarian response in terms of shelter, food, sanitation and health. 13000+ Palestinian children (alone) have been brutally massacred in the name of fishing Hamas militants from Gaza. It leads to the inevitable question brimming globally, if it ever would end. The answer lies in the article, a Muslim onlooker’s perspective on how Western entities of power nail onto their agenda via violence, even when it completely surpasses and negates all criteria of social justice and human rights in 2024, because: ‘ A right delayed, is a right denied.’- Martin Luther King.